The Influence of Leadership Style, Work-Life Balance and Career Development on Employee Performance at The Palopo City Land Office - Nur Zamzam; Suhardi M Anwar; Junaidi Junaidi (LP3M Universitas Putra Bangsa, 2025)
The purpose of this study is to study how leadership style, work-life balance, and career development have an impact on employee performance at the Palopo City Land Office. Data were collected through questionnaires and analyzed using validity, reliability, multiple linear regression tests, t test, f test, and r2 test. The results showed that the independent variable had a positive and significant impact on employee performance, although there were also those that did not have a positive impact on employee performance According to this study, organizations should consider leadership style, work-life balance, and career development if they want to improve employee performance.